Step
*
3
1
1
of Lemma
arctan_wf1
1. ∀x:ℝ. (r0 < (r1 + x^2))
2. x : ℝ
3. arctan(x) ∈ {y:ℝ| y = full-arctan(x)} 
4. arctan(x) = arctan(x) ∈ {y:ℝ| y = full-arctan(x)} 
5. x1 : ℝ
6. x1 = full-arctan(x)
⊢ full-arctan(x) = arctangent(x)
BY
{ (GenConclTerm ⌜full-arctan(x)⌝⋅ THEN Auto) }
Latex:
Latex:
1.  \mforall{}x:\mBbbR{}.  (r0  <  (r1  +  x\^{}2))
2.  x  :  \mBbbR{}
3.  arctan(x)  \mmember{}  \{y:\mBbbR{}|  y  =  full-arctan(x)\} 
4.  arctan(x)  =  arctan(x)
5.  x1  :  \mBbbR{}
6.  x1  =  full-arctan(x)
\mvdash{}  full-arctan(x)  =  arctangent(x)
By
Latex:
(GenConclTerm  \mkleeneopen{}full-arctan(x)\mkleeneclose{}\mcdot{}  THEN  Auto)
Home
Index